Phytochemical screening and antifungal activity of Chromolaena odorata extracts against isolate of Phytophthora megakarya using agar-well diffusion method - Adeyemi, Adeyemo I; Vincent, Omotunlese I; Olujenyo, Oni M (Asian Journal of Medical and Biological Research, 2018)
In-vitro study of Chromolaena odorata extracts was determined against isolated Phytophthora megakarya for the purpose of investigating the antifungal activity of ethanolic, cold-water and warm-water extracts of the medicinal plant against Phytophthora megakarya. Their antifungal effects were assessed with agar-well diffusion methods. Phytochemical screening and minimum inhibitory concentrations of the extracts were also determined. A qualitative phytochemical analysis of the extracts showed the presence of biologically active constituents such as flavonoids, phenols, tannins, sterols, amino acid and glycosinulate. Results showed that antifungal effects of Chromolaena odorata against Phytophthora megakarya were most efficient by ethanolic extracts, followed by extract of cold-water while hot water extract had no visible antifungal effect. Zones of clearance range from 15.00 mm to 32.00 mm using ethanolic extractions with concentrations from 1% to 5% while zones of clearance using cold water extract was from 5.00 mm to 30.00 mm with varying concentrations of 1% to 5%. The negative control using sterile distilled water showed no inhibitory effect on Phytophthora megakarya while 41.00 mm zone of clearance was observed in the positive control test using Metalaxyl and cuprous oxide-containing synthetic fungicide. This study provides a scientific confirmation of the use of Chromolaena odorata against cocoa pod infections by some local farmers. Asian J. Med. Biol. Res. March 2018, 4(1): 7-13